A Consumption Model of Income Inequality - Wessels, Walter J. (Journal of Income Distribution®, 2008)
This article focuses on the inequality of incomes between the very rich and the rest of society. Accordingly, it measures inequality as the ratio of the share of national income of the top five percent of households over the share of the rest of society. It shows that this measure of inequality increases when productivity grows in the manufacturing sector and decreases when productivity grows in the nonmanufacturing sector. These results suggest the rich earn relatively more when productivity lags in the nonmanufacturing sector. A model is presented that provides an explanation for these results. With complete markets, risk-averse individuals will hold a portfolio of assets that effectively produces the goods they intend to consume in order to insure they get the consumption mix they want. Since the rich spend relatively more on superior goods, they will hold relatively more assets in the superior good sector. When productivity grows in the necessity sector, the relative price of superior goods increases and the rich, holding relatively more of the assets producing superior goods, will become richer. The opposite occurs when productivity grows in the superior-good sector. Evidence suggests that nonmanufactured goods are superior goods.